Should licking behavior be considered in the bioavailability evaluation of transdermal products? - Toutain, P. L. (2012)
Antiparasitic drugs, and especially macrocyclic lactones (MLs), are often formulated as pour-on products because of their ease of administration, convenience, and reduction of stress in treated animals. However, because of self- and allo-grooming, much of a drug administered transdermally may be systemically absorbed via the oral route, creating highly variable pharmacokinetic and pharmacodynamic response in treated (and untreated) animals. Testing bioequivalence (BE) of pour-on drugs in cattle under laboratory conditions (with restricted licking) ignores a major factor of drug disposition of these drugs and thus fails to predict therapeutic equivalence in the target population under clinical conditions of use. Therefore, the interanimal and intra-animal variability associated with licking behavior should be considered as a biological fact, rather than a noise that needs to be reduced or eliminated. As a result, it is recommended that the BE testing for pour-on products in cattle be conducted by evaluating both the mean and distribution of bioavailability parameters between the reference and test products when animals are not prevented from allo- and self-licking.